PENGARUH KOMPENSASI DAN KOMPETENSI DENGAN MOTIVASI SEBAGAI INTERVENING DALAM MENINGKATKAN KINERJA - Meutia, Meutia; Sari, Ika; Ismail, Tubagus (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2016)
The objective of this research was to test the impact of system financial and nonfinancial compensation, competency on the employee performance and on the motivation as intervening variable. The research used partial least square method for the hypotesis testing and produced 100 respondent for the sample by using nonprobability samples with the convinience method. The result of the research revealed that the system of financial and nonfinancial compensation have significance impacts on employee performance and motivation but the competency does not Ã‚Â significance impacts on employee performance and motivation. However, further result revealed that motivation have significance impacts on employee performance.In order to improve the employee performance, the training is a needed and should be conducted in accordance with the job position. Moreover, the fair compensation with the range not far from the employee expectation.